Talent management - Collings, David (Henry Stewart Talks, 2012)
Context of talent management, Definition, Talent management as a substitute for HRM, Development of talent pools, The management of talented people, The identification of key positions, Collings & Mellahi definition, Strategic talent management, Pivotal talent positions, Developing a talent pool, A differentiated HR architecture, The challenges of managing star employees, Defining talent, Identifying high potential, Implications of disclosure, Negative implications of the war for talent, Emphasising the individual over the team, Predicting star performance, Glorification of outsiders, The self-fulfilling prophecy, The way forward
Reviewed at 2019/11/28